PENINGKATAN KREATIFITAS DAN RASA CINTA LINGKUNGANTERHADAP ANAK DENGAN MEDIA PEMBUATAN BONEKA HORTA - Siti Hapsah Isfardiyana (Asian Journal of Innovation and Entrepreneurship, 2014)
Horta doll is one new breakthrough which could be used as a medium of learningfor children to be able to understand the insights loving environment. These dolls canalso be used as a medium to develop the creativityof children because it can be shapedin various forms. The concept is to use items that are no longer used can also teachchildren to manage waste properly. The program to improve creativity and love of theenvironment on children by making horta dollscan be one way to introduce children tothe environment, plants, thrift can still have value when create it and foster children atthe gardening craze.